2018
DOI: 10.1007/s00428-018-2433-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of HER2 gene amplification and tumor progression in early gastric cancer

Abstract: Overexpression of human epidermal growth factor receptor 2 (HER2) protein in association with HER2 gene amplification is found in 7-34% of gastric cancers. In breast cancer, HER2 overexpression is a prognostic factor in advanced cases and is associated with tumor progression in ductal carcinoma in situ. However, the biological and clinical significance of HER2 status in early gastric cancer is unknown. Here, we aimed to examine the correlation between HER2 gene amplification and tumor progression in early gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Of note, none of the biomarkers identified in metastatic patients were prospectively validated in randomized clinical investigations in localized gastric cancer. However, angiogenesis, HER2 amplification, MSI, and EBV+ status are early events in the development of gastric cancer [969899] and it is reasonable to conceive that their predictive value could be relevant also in the preoperative setting. The ongoing clinical trials of perioperative systemic therapies in localized gastric cancer will provide an answer to these questions.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, none of the biomarkers identified in metastatic patients were prospectively validated in randomized clinical investigations in localized gastric cancer. However, angiogenesis, HER2 amplification, MSI, and EBV+ status are early events in the development of gastric cancer [969899] and it is reasonable to conceive that their predictive value could be relevant also in the preoperative setting. The ongoing clinical trials of perioperative systemic therapies in localized gastric cancer will provide an answer to these questions.…”
Section: Resultsmentioning
confidence: 99%
“…Intrapatient discordance rates between the primary tumor and metastases ranging from 2-24% [30][31][32] as well as intratumoral discordance rates [33,34] represent potential pitfalls of HER2 testing. Intratumoral HER2 expression heterogeneity can be found in up to 74% in early gastric cancer [35]. Neoplastic clonal selection with HER2 amplification in otherwise HER2 negative tumors as well as HER2 silenced tumor areas in cases with homogeneous HER2 amplification have been proposed as mechanisms leading to HER2 expression heterogeneity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for HER2 and p53 were performed as previously described 7,8 . Briefly, HER2 was evaluated using an automated slide stainer (Bench‐Mark XT; Ventana Medical Systems, Tucson, AZ, USA), anti‐HER2 antibodies (clone 4B5; Ventana Medical Systems), and an iView DAB detection kit (Ventana Medical Systems).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms of HER2 heterogeneity are not fully understood. In a previous study, we examined HER2 heterogeneity in individuals using immunohistochemistry (IHC) and dual‐color in situ hybridization (DISH) in the same area and revealed correlation between HER2 protein overexpression and HER2 gene amplification 7,8 . Additionally, we showed that HER2 heterogeneity was observed in subpopulations of cells, even in early stage gastric cancers, and may be maintained during tumor progression 8 …”
Section: Introductionmentioning
confidence: 98%